1990
DOI: 10.1002/iroh.19900750608
|View full text |Cite
|
Sign up to set email alerts
|

Age Determination of Eels in the French Mediterranean Lagoons Using Classical Methods and an Image Analysis System

Abstract: Abstra'ctSeveral methods are used for age determination of eels in the French mediterranean lagoons (observation of the whole otolith after clearing, grinding and polishing, dyeing, SEM and image analysis). Two types of otoliths &re observed depending on the width of the growth rings which is probably related to the environmental conditiona. Furthermore, the growth checks are located nearby or inside the opaque rings. A computer assisted method is developed, with reference to the other methods, with the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…As far as the relation between environment conditions and otolith growth of A. anguilla is concerned, our results appear consistent with Panfili et al (1990) observation of two different types of sagittae, dependent on the width of the growth rings, which they called "brackish water type" and "freshwater type" otolith, respectively. Indeed, the periodicity and the width of the increments due to deposition are regulated by endogenous factors but also depend upon features such as temperature fluctuations and feeding (Campana and Neilson, 1985;Morales-Nin, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…As far as the relation between environment conditions and otolith growth of A. anguilla is concerned, our results appear consistent with Panfili et al (1990) observation of two different types of sagittae, dependent on the width of the growth rings, which they called "brackish water type" and "freshwater type" otolith, respectively. Indeed, the periodicity and the width of the increments due to deposition are regulated by endogenous factors but also depend upon features such as temperature fluctuations and feeding (Campana and Neilson, 1985;Morales-Nin, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…2a). A partir de l'observation «in toto», les techniques de traitement numérique (analyse d'image) permettent d'accentuer les différences de densités optiques entre les zones sous forme de niveaux de gris, et de caractériser les anneaux opaques et hyalins par les maxima et les minima respectivement (PANFILI et al, 1990 ;PANFILI, 1993). Le comptage et les mesures des zones de croissance peuvent alors être réalisés * La validation est la vérification expérimentale des hypothèses sur les scénarios de croissance des marques sur les pièces dures. "…”
Section: Mise En éVidence Et Interprétation Des Structures Pour Estimunclassified
“…By using the relationship between fish length and otolith dimensions it is possible to not only identify fish species and fish stock, but also to estimate characteristics such as fish size, age, prey size (from stomach samples and analysis of digestive tract content) and feeding habits (DEHGHANI et al, 2015). PANFILI et al (1990) and CAPOCCIONI et al (2011) reported two different types of sagittae of eel, depending on the width of the growth rings, which they called "brackish water type" and "freshwater type"otolith, respectively.…”
Section: Introductionmentioning
confidence: 99%